Alterations in blood Lipoprotein & Apolipoprotein B profile induced by moderate acute & chronic alcohol intake in the rat model. (c2002) - Berberi, Rania (2002)
The studies reported here evaluated the effects of acute and chronic 3% alcohol intake from either beer or whisky in drinking water upon blood lipids, lipoproteins and apolipoprotein B (apo B) profiles in the fasted and postprandial states. In the acute alcohol study, the co-administration of a whisky dose with the fat load resulted in significant increases in plasma triacylglycerol (TAG) and cholesterol concentrations. Similarly, chylomicron TAG, cholesterol, phospholipids and apo B48 as well as VLDL TAG, apo B48 and apo B 1 00 were also significantly increased. When the whisky dose was replaced by an equivalent ethanol dose, results exhibited similar trends but without being consistently significant. On the other hand, a 3% alcohol consumption (as beer or whisky) maintained for a two months period did not have an effect on fasting plasma TAG concentration while total and LDL cholesterol concentrations showed a significant decrease and HDL cholesterol concentration was moderately increased. Fasting plasma glucose concentrations were significantly increased in both alcohol-tested groups whereas fasting plasma insulin was significantly increased in the beer group and not affected in the whisky group. Moreover, in the two and six months chronic postprandial alcohol studies, there were no consistent significant increases in plasma TAG and cholesterol concentrations and plasma glucose concentration was apparently not affected. In the two months chronic study, TAG, cholesterol and phospholipid concentrations were slightly increased in the chylomicron fractions of both beer and whisky groups while apo B48 concentrations were significantly increased in both groups relative to control. In the six months chronic study, chylomicron TAG, cholesterol, phospholipid and apo B48 concentrations of both alcohol-tested groups were significantly higher than that of the control group. Moreover, VLDL TAG concentrations and apo B48 and apo B 100 secretion were increased as a result of chronic alcohol consumption. Therefore, despite reported correlations between the obtained increases in chylomicron and VLDL plasma concentrations and atherogenesis, this study suggests that the reduced amount of cholesterol per newly secreted VLDL particle and their increased catabolic rate will ultimately lead to a reduced total and LDL cholesterol concentrations in the fasted state. This latter finding, in addition to the observed modest increase in HDL cholesterol, suggests a cardioprotective effect induced by chronic moderate alcohol consumption.